1990
DOI: 10.1002/pssa.2211200119
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structure and Spin-Orientational Transitions of Hexaferrites of the BaCo2−xZnxFe16O27 System

Abstract: A neutronographic study is made of magnetic structure and spin‐orientational transitions in polycrystalline samples of the system BaCo2−xZnxFe16O27 (Co2−xZnxW). Along with this studies measurements of the macroscopic magnetic characteristics, X‐ray dilatometry, and DTA are performed. The diagram of the magnetic state is plotted in the coordinates: content‐temperature. The compounds with Zn2+ ion content, 0 ≦ x ≦ 1.6 exhibit the sequence of orientational phase transitions coneplane‐cone‐axis of easy magnitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
(1 reference statement)
2
24
0
Order By: Relevance
“…To establish correct functioning of the Virtual Instrument program it is necessary to measure the effect of temperature on the magnetic permeability of W-type hexaferrite powder [5]. The hexaferrite powder was put into quartz tube with inner diameter 2 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish correct functioning of the Virtual Instrument program it is necessary to measure the effect of temperature on the magnetic permeability of W-type hexaferrite powder [5]. The hexaferrite powder was put into quartz tube with inner diameter 2 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the calculation results. In order to provide an interpretation of the magnetic permeability results, we will use a data from article [5]. This article shows, that W-type hexaferrite bulk sample have nonlinear temperature dependence of magnetic permeability.…”
Section: Resultsmentioning
confidence: 99%
“…It is natural that with increasing cobalt ion content, the spin reorientation phase transition from EMD to EMP type anisotropy will be observed in solid solutions of the Co 2+ -containing hexaferrites combined with any of the above-listed ions. We note that these transitions are observed not only for concentration but also for temperature changes [2][3][4]. Neutron-diffraction investigations of Co 2-x Zn x W system hexaferrites carried out in [3] have demonstrated that the EMD ↔ EMP temperature spin reorientation transition proceeds through the easy magnetization cone (EMC) phase.…”
Section: Introductionmentioning
confidence: 92%
“…We note that these transitions are observed not only for concentration but also for temperature changes [2][3][4]. Neutron-diffraction investigations of Co 2-x Zn x W system hexaferrites carried out in [3] have demonstrated that the EMD ↔ EMP temperature spin reorientation transition proceeds through the easy magnetization cone (EMC) phase. The anisotropy fields can change in a wide range with changes of the Co 2+ ion concentration, which offers possibilities of W-type hexaferrite application for EWA in the entire microwave range starting from ~1 GHz [4,5].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation